The extent of the impact of information technology governance and its application mechanisms on the quality of accounting information in bank accounts - the Cobit framework as a model - Sakhil, Amel Merzah; Jabal, Shaymaa Nihro; Najm, Naseer Faisal (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
IT governance is an element of corporate governance, aims to improve the general management of information technology and extract improved value from investment in information and technology, and has a great role to play in improving the quality of accounting information. In order to provide quality information technology and oversight practices that contribute to strengthening the Department's needs in determining the appropriate level of information technology security and follow-up, An appropriate framework has to be applied that contributes to linking information technology with various operations in financial institutions, helping to reduce gaps between different departments and reduce risks. Through the application of one of the mechanisms of IT governance framework COBiT, and the research problem was knowing the extent to which IT governance and the mechanisms for applying it to the quality of accounting information in bank accounts using (Cobit Framework) Model, BaseResearch into a fundamental hypothesis, IT governance and application mechanisms affect the quality of accounting information in bank accounts using The research has reached a number of conclusions, the most important of which are: The bank has oversight agencies and procedures to ensure compliance with the rules and laws on the governance of information technology technology to improve the efficiency of the business, which in turn contributes to the quality of accounting information in bank accounts. The research recommended that there should be a formal framework for managing the risks of information technology at the bank, which would result in a lack of identification of the relevant risks and plans to reduce them. The study included supplements complementing research purposes followed by a list of research sources.